2015
DOI: 10.1088/0953-4075/48/15/155203
|View full text |Cite
|
Sign up to set email alerts
|

Observation of two-center interference effects for electron impact ionization of N2

Abstract: In 1966, Cohen and Fano (1966 Phys. Rev. 150 30) suggested that one should be able to observe the equivalent of Young's double slit interference if the double slits were replaced by a diatomic molecule. This suggestion inspired many experimental and theoretical studies searching for double slit interference effects both for photon and particle ionization of diatomic molecules. These effects turned out to be so small for particle ionization that this work proceeded slowly and evidence for interference effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…True coincidences are selected by setting conditions on the peak in the coincidence time spectrum. Further experimental details may be found in [30]- [33].…”
Section: -Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…True coincidences are selected by setting conditions on the peak in the coincidence time spectrum. Further experimental details may be found in [30]- [33].…”
Section: -Experimental Proceduresmentioning
confidence: 99%
“…A summary of this work up to 2010 was given by Madison and Al Hagan [19]. More recently, studies have been performed for ionization of CH 4 [20], [21], tetrahydrofuran and tetrahydrofurfuryl [22], NH3 [23], the cyclic ethers tetrahydrofuran, tetrahydropyran and 1,4-dioxane [24], tetrahydropyran and 1,4-dioxane [25], phenol [26], N 2 [27], ethane [28], and furfural [29]. The M3DW has not been previously applied to CO 2 .…”
mentioning
confidence: 99%
“…They calculated the recoil and binary peak ratios for the outer orbitals of the N2 molecule, 3σg, 1πu, 2σ, using the model they produced. In a study to examine interference effects, Chaluvadi et al [18]. With this study, results showing that interference effects are observed as a result of ionization of nitrogen molecule for the first time in the literature.…”
Section: Introductionmentioning
confidence: 76%
“…The DWBA formalism along with the orientation averaged molecular orbital approximation is capable to produce reliable TDCS results at the incident electron energy 250 eV used in the present study [11,56]. The DWBA has been very successful at the higher energies [9], however the DWBA with PCI effects have been found successful at the intermediate energies also [56].…”
Section:  mentioning
confidence: 94%